Comparison of Waiting and Consultation Times in Convenient Care Clinics and Physician Offices - Avinash Patwardhan; Jeffery Davis; Patricia Murphy; Sandra Festa Ryan (SAGE Publishing, 2013)
This study measures waiting times and consultation times at convenient care clinics (CCCs), and compares them with equivalent times in traditional, family practice, physician offices. The analysis was limited to conditions most commonly treated at CCCs. It was found that patients using CCCs had significantly shorter waiting times from check-in to seeing a clinician than the equivalent waiting times reported by patients at family practice physicians' offices and that CCC patients had significantly longer consultation times with the clinician than those reported by family practice patients. Applying a correction factor to adjust for potential differences between real waiting times and perceived waiting times did not substantially alter the conclusions. Shorter waiting times may increase satisfaction and thereby encourage patients to seek care; and spending additional time with the clinician may help ensure that all of a patient's concerns or questions are addressed. This study provides objective evidence from a large database that CCCs provide prompt, satisfying care.